Analisis Pengaruh Variasi Jarak Tray terhadap Kinerja Tray Aerator dalam Menurunkan Kandungan Besi dan Mangan pada Air Sumur - Puspitasari, Ratna Endah Dwi; Euis Nurul Hidayah (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
This study aims to analyse the effect of tray spacing variations on the performance of tray aerators in reducing iron (Fe) and manganese (Mn) concentrations in well water. A quantitative experimental method was used with three tray spacing variations (30 cm, 40 cm and 60 cm) and different tray levels. The results indicate that the tray aerator with 40 cm tray spacing achieved iron removal efficiencies of up to 85.83% and manganese removal efficiencies of up to 35.14%, outperforming other spacing configurations. Tray spacing and aeration time were found to have a significant effect on removal efficiency, with 40 cm spacing providing an optimum balance between turbulence and contact time. In addition, the highest increase in dissolved oxygen (DO) occurred at 30 cm tray spacing. This study concludes that proper tray spacing arrangements can improve the effectiveness of tray aerators in treating well water.